Consent Form Readability and Educational Levels of Potential Participants in Mental Health Research - Christopher, Paul P; Foti, Mary Ellen; Roy-Bujnowski, Kristen; Appelbaum, Paul S (Psychiatric services (Washington, D.C.), 2007)
Poor readability of informed consent forms has been a persistent problem in clinical research. The low educational attainments of many patients with mental illness might suggest a still greater problem in mental health settings. To explore this potential disparity, this study sought to determine whether the informed consent forms used in research approved by the Massachusetts Department of Mental Health were written at a grade level that was higher than that achieved by potential study participants. The readability (grade level necessary to read text) of informed consent forms for 154 studies was calculated with several standard formulas. Readability scores were stratified on the basis of the risk level of the study from which the consent form was taken. These data were then compared with data on the maximum attained grade level of potential participants aged 19 years or older. The overall mean readability scores for the informed consent forms, as determined by the four methods, ranged from grade levels 12 to 14.5. Furthermore, the mean readability scores increased with higher risk levels of the studies. Approximately 35% of potential participants had not graduated from high school, 37% had graduated from high school or obtained a GED, and 28% had some education beyond the 12th grade. These data demonstrate poor readability of informed consent forms used in research approved by the Massachusetts Department of Mental Health and highlight a mismatch between consent form readability and the educational level of potential study participants. The findings suggest that methods of reducing the complexity of forms, as part of improving the overall consent process, are much needed.